The importance of social capital in protracted displacement - Uzelac, A; Meester, J; Goransson, M; van den Berg, W (Refugee Studies Centre, University of Oxford, 2018)
By understanding the role that social capital plays in the lives of Syrian refugees in Lebanon – how it is created, sustained, converted and what happens when it breaks down – we hope to generate discussion about ways to further tailor assessments, targeting and programming in this and other situations of protracted displacement.